2009
DOI: 10.1645/ge-1592.1
|View full text |Cite
|
Sign up to set email alerts
|

Dactylogyrids (Monogenoidea) Parasitizing the Gills of Astyanax Spp. (Characidae) From Panama and Southeast Mexico, a New Species of Diaphorocleidus and a Proposal for Characithecium N. Gen

Abstract: Diaphorocleidus orthodusus n. sp. and Diaphorocleidus kabatai (Molnar, Hanek and Fernando, 1974) Jogunoori, Kritsky, and Venkatanarasaiah, 2004 are detailed from Astyanax orthodus and Astyanax aeneus, respectively. Palombitrema heteroancistrium (Price and Bussing, 1968) is described from specimens collected from A. aeneus, and Urocleidoides strombicirrus (Price and Bussing, 1967) is reported for the first time from A. aeneus and Astyanax fasciatus in Panama. Characithecium costaricensis (Price and Bussing, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…and Gyrodactylus spp (see Hoffman 1999), needs to be determined with more survey work in northern regions of Mexico. Although, recent studies by monogenean taxonomists have demonstrated that the species richness of this parasitic group in freshwater fishes of Mexico is increasing very rapidly (see Kritsky and Mendoza-Franco 2003;Mendoza-Palmero and Aguilar-Aguilar 2008;Mendoza-Franco et al 2009;Mendoza-Palmero et al 2009). From a biogeographical perspective, it is also possible that the Nearctic freshwater fish host a larger proportion of adult helminth parasites than larval forms.…”
Section: Methodsmentioning
confidence: 99%
“…and Gyrodactylus spp (see Hoffman 1999), needs to be determined with more survey work in northern regions of Mexico. Although, recent studies by monogenean taxonomists have demonstrated that the species richness of this parasitic group in freshwater fishes of Mexico is increasing very rapidly (see Kritsky and Mendoza-Franco 2003;Mendoza-Palmero and Aguilar-Aguilar 2008;Mendoza-Franco et al 2009;Mendoza-Palmero et al 2009). From a biogeographical perspective, it is also possible that the Nearctic freshwater fish host a larger proportion of adult helminth parasites than larval forms.…”
Section: Methodsmentioning
confidence: 99%
“…3). In the same way, the continuous description of new species, named and described based on morphological taxonomy [47], [48], [49], [50] points out that even in the best studied drainage basins and fish families, the inventories are far from complete. Particularly, the study of Mexican monogeneans of freshwater fishes remains a challenge for taxonomists.…”
Section: Discussionmentioning
confidence: 99%
“…These monogeneans were first described parasitizing the gills of Astyanax spp. (Mendoza-Franco et al, 2009), and there is only one report of D. kabatai parasitizing A. altiparanae Garutti andBritsky, 2000 (Almeida andCohen, 2011). Thus, this study corroborates the literature and strongly suggests the specificity of these monogeneans with the genus Astyanax.…”
Section: Discussionmentioning
confidence: 99%